Exploration of the acarine fauna on coconut palm in Brazil with emphasis on Aceria guerreronis (Acari: Eriophyidae) and its natural enemies - Lawson-Balagbo, L.M.; Gondim, M.G.C.; Moraes, G.J. de; Hanna, R.; Schausberger, P. (2008)
Coconut is an important crop in tropical and subtropical regions. Among the mites that infest coconut palms, Aceria guerreronis Keifer is economically the most important. We conducted surveys throughout the coconut growing areas of Brazil. Samples were taken from attached coconuts, leaflets, fallen coconuts and inflorescences of coconut palms in 112 localities aiming to determine the occurrence and the distribution of phytophagous mites, particularly A. guerreronis, and associated natural enemies. Aceria guerreronis was the most abundant phytophagous mite followed by Steneotarsonemus concavuscutum Lofego & Gondim Jr. and Steneotarsonemus furcatus De Leon (Tarsonemidae). Infestation by A. guerreronis was recorded in 87% of the visited localities. About 81% of all predatory mites belonged to the family Phytoseiidae, mainly represented by Neoseiulus paspalivorus De Leon, Neoseiulus baraki Athias-Henriot and Amblyseius largoensis Muma; 12% were Ascidae, mainly Proctolaelaps bickleyi Bram, Proctolaelaps sp nov and Lasioseius subterraneus Chant. Neoseiulus paspalivorus and N. baraki were the most abundant predators on attached coconuts. Ascidae were predominant on fallen coconuts, while A. largoensis was predominant on leaflets; no mites were found on branches of inflorescences. Leaflets harboured higher mite diversity than the attached coconuts. Mite diversity was the highest in the state Pará and on palms surrounded by seasonal forests and Amazonian rain-forests. Neoseiulus paspalivorus, N. baraki and P. bickleyi were identified as the most promising predators of A. guerreronis. Analyses of the influence of climatic factors revealed that dry ambient conditions favour the establishment of A. guerreronis. Neoseiulus paspalivorus and N. baraki have differing climatic requirements; the former being more abundant in warm and dry areas, the latter prevailing in moderately tempered and humid areas. We discuss the significance of our findings for natural and biological control of A. guerreronis.